2020
DOI: 10.1111/phpp.12537
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the minimal erythema dose for UVB and UVA in context of skin phototype and nature of photodermatosis

Abstract: BackgroundPhototesting is part of the standard procedure for the evaluation of patients with photosensitivity disorders. The response of patients to targeted UVB or UVA radiation helps to find out more about the nature of photodermatosis. Nevertheless, there are no default values of the minimal erythema dose (MED).MethodsThis study evaluated data of 203 patients (131 female, 72 male, mean age 52 years) who were referred for phototesting to the University Hospital Zurich between 2012 and 2017. We retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Patient #4 exhibited initial negative phototesting results, but his prototypical clinical features and histopathologic findings were deemed most consistent with chronic actinic dermatitis. These findings are in keeping with recently reviewed data demonstrating that a significant number of patients with a wide range of clinically diagnosed photodermatologic disorders do not exhibit reduced minimal erythema dose (MED) values at the time of phototesting 3 …”
Section: Report Of a Case Seriessupporting
confidence: 87%
“…Patient #4 exhibited initial negative phototesting results, but his prototypical clinical features and histopathologic findings were deemed most consistent with chronic actinic dermatitis. These findings are in keeping with recently reviewed data demonstrating that a significant number of patients with a wide range of clinically diagnosed photodermatologic disorders do not exhibit reduced minimal erythema dose (MED) values at the time of phototesting 3 …”
Section: Report Of a Case Seriessupporting
confidence: 87%
“…The strengths of the study, making it translationally relevant, are as follows: We tested HCTZ in a range of concentrations reflecting the plasma levels of doses used in clinical practice [ 25 , 26 ]; despite the lack of data on the accumulation of HCTZ in the skin, it is reasonable that HCTZ reaches the skin in a sufficient amount since patients taking HCTZ often experience cutaneous photosensitivity reactions; the use of therapeutic concentrations is also relevant for mimicking the actual human exposure. We applied a cumulative weekly UVA dose of 20 J/cm 2 that mimics a human exposure of approximately 1 hour to midsummer sun in Paris [ 27 ], and it is below the UVA minimal erythema dose for I-II skin phototypes [ 77 ]; moreover, the long-term treatment resembles the multiple irradiations and chronic HCTZ treatment that may drive the cancerogenic process from cells able to survive upon insults and transform. The morphological and molecular features described resemble some aspects of dysplastic lesions described by Coussens and Hanahan [ 78 ] in a mouse model of squamous carcinoma and, at least in part, those found in precursor lesions and in nonmelanoma skin cancers in humans.…”
Section: Limitations and Strengths Of The Studymentioning
confidence: 99%
“…We applied a cumulative weekly UVA dose of 20 J/cm 2 that mimics a human exposure of approximately 1 hour to midsummer sun in Paris [ 27 ], and it is below the UVA minimal erythema dose for I-II skin phototypes [ 77 ]; moreover, the long-term treatment resembles the multiple irradiations and chronic HCTZ treatment that may drive the cancerogenic process from cells able to survive upon insults and transform.…”
Section: Limitations and Strengths Of The Studymentioning
confidence: 99%
“…The photosensitivity to UVA is common and some scholars infer that this is due to the wavelengths of light that cause activation of most photoallergens lies in the UVA range because it penetrates more deeply into the skin than UVB, enabling its interaction with chemicals whose biodistribution is in deeper levels of cutaneous tissue 6 . Moreover, according to the study of Welti et al, 7 the MED‐UVA is reduced in subjects with some photodermatosis (polymorphous light eruption, solar urticaria, rosacea, and among others) compared with controls. Correspondingly, in our study, MED‐UVA was lower in melasma patients with phototypes Ⅲ and Ⅳ than in unaffected controls.…”
Section: Discussionmentioning
confidence: 99%
“…Although PhPT is more valuable when photosensitivity is suspected, the determination of the MED is more helpful for the diagnosis 6 . Previous studies demonstrated that patients with photodermatosis exhibit lower MED levels than controls without photodermatosis, suggesting a relationship between the MED and photodermatosis 7 . Verallo‐Rowell et al 8 observed a higher rate of positive reaction to visible light PhPT in patients with melasma than in controls, indicating that those with melasma may have a higher photosensitivity than unaffected individuals.…”
Section: Introductionmentioning
confidence: 99%